(untitled) (Itinera, 2020)
Observing the phenomenon of cultural appropriation in a case of theatre: Kanata the controversial spectacle by the Québecois Robert Lepage raises issues of aesthetics. The specific cultural, political and social context, together with the singularity of theatre as an art form, makes this a unique case study shedding light on that phenomenon and causing us to rethink some long-standing principles of aesthetics.